Efek Antihipertensi dan Hipotensi beberapa Fraksi dari Ekstrak Etanol Umbi Lapis Kucai (Allium schoenoprasum L., Lliliaceae) - Irda Fidrianny; Kosasih Padmawinata; Soediro Soetarno; Elin Yulinah (Jurnal Matematika & Sains, 2003)
Hypotensive and antihypertensive effect of fractions of ethanolic extract of âkucaiâ (Allium schoenoprasum L., Liliaceae) bulb had been tested on male Wistar rats. The ethyl acetate, n-buthanol and aqueous fractions of both fresh and dry bulb had hypotensive and antihypertensive effects. The aqueous fraction of fresh bulb at a dose of 25 mg/kg body weight showed the highest hypotensive and antihypertensive activities. The n-buthanol fraction of dry bulb at a dose of 50 mg/kg body weight showed the highest hypotensive activity. The ethyl acetate fraction of dry bulb at a dose of 50 mg/kg body weight showed the highest antihypertensive activity.